PELATIHAN PENGGUNAAN ALAT PELINDUNG DIRI PADA PERAWAT DI RUANG RADIOLOGI RUMAH SAKIT UMUM SEMBIRING - Herlina J. El-Matury; Elisabeth Dame Manalu; Saiful Batubara (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
In medical, radiation exposure hazard in radiology rooms is higher than other places. Nurses who are exposed to radiation for a long time and continuously can cause health problems due to radiation exposure to nurses in the radiology room. Sembiring Hospital plays an important role in the management system to avoid and reduce radiation exposure hazards. The results of level of compliance and the behavior of using Personal Protective Equipment, out of 30 radiology room nurses, 80% of them did not comply with wearing Personal Protective Equipment when working due to lack of knowledge and awareness. Therefore, it’s necessary to provide health education and training to change the behavior of the use of Personal Protective Equipment. By conducting training of using Personal Protective Equipment and counseling about the dangers of radiation and the importance of using Personal Protective Equipment to nurses who work in the radiology room, it’s hoped that they can increase their knowledge and their ability. This training and counseling forms a mindset and awareness. With the creation of a mindset to be aware, nurses can form compliance with Personal Protective Equipment while working without having to be supervised by the Health Safety Environment Officer at the Sembiring Hospital